Synthesis and characterization of the Bi2-xHox/2Zr3x/8O3 compounds - Šulcová P.; Bystrzycki P.; Válek L.; Trojan M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A series of novel environmentally inorganic pigments based on Bi2O3 doped by metal ions such as Zr4+ and Ho3+ have been developed and characterized using of methods of thermal analysis, Xray powder diffraction and CIE L